2018
DOI: 10.1038/s41598-018-32055-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cycle microorganisms can be reactivated after Space exposure

Abstract: Long-term human Space missions depend on regenerative life support systems (RLSS) to produce food, water and oxygen from waste and metabolic products. Microbial biotechnology is efficient for nitrogen conversion, with nitrate or nitrogen gas as desirable products. A prerequisite to bioreactor operation in Space is the feasibility to reactivate cells exposed to microgravity and radiation. In this study, microorganisms capable of essential nitrogen cycle conversions were sent on a 44-days FOTON-M4 flight to Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…If a more thorough characterization of the biomass at cell level in terms of average cell dimension and biovolume would be performed, it could permit a better correlation between VSS and FCM results. Similar to previous work, a correlation between protein measurements following the Lowry method and VSS could also provide additional characterization (Lindeboom et al, 2018). Moreover, if these incubations are monitored with online pH, pressure measurements and intensive sampling for microbial community dynamics, a clearer correlation could be obtained between changes in the community and operational variables modified by the pressurized operation.…”
Section: Discussionmentioning
confidence: 64%
“…If a more thorough characterization of the biomass at cell level in terms of average cell dimension and biovolume would be performed, it could permit a better correlation between VSS and FCM results. Similar to previous work, a correlation between protein measurements following the Lowry method and VSS could also provide additional characterization (Lindeboom et al, 2018). Moreover, if these incubations are monitored with online pH, pressure measurements and intensive sampling for microbial community dynamics, a clearer correlation could be obtained between changes in the community and operational variables modified by the pressurized operation.…”
Section: Discussionmentioning
confidence: 64%
“…The synthetic communities with both AOB and NOB were provided with a substrate concentration of 80 mg-N L -1 of NH 4 Cl (5.7 mM of NH 4 + ) and 80 mg-N L -1 of NaNO 2 (5.7 mM of NO 2 - ) to evaluate the ammonia and nitrite oxidation rates, respectively, while the pure strains were fed only with 80 mg-N L -1 of NH 4 Cl for the AOB and 80 mg-N L -1 of NaNO 2 for the NOB. All the activity tests were performed in triplicate, as reported by Lindeboom et al (2018) . For each culture, 250 μL duplicates were prepared in a sterile flat-bottom 96-well plate and incubated at 28°C in the dark, in a Thermoshaker (MB100-4A, Thermoshakers Aosheng, China) for up to 6 days or until complete consumption of the substrate.…”
Section: Methodsmentioning
confidence: 99%
“…While a combination of ureolysis and nitrification has been repeatedly demonstrated with open communities (e.g., De Paepe et al, 2018;Muys et al, 2018), this has not yet been reported with reductionistic synthetic communities. Since ammonia oxidation is commonly considered the limiting step of nitrification, so far little focus has been reserved to the complete urea hydrolysis and subsequent nitrification process, with only one synthetic community being described (Lindeboom et al, 2018). To include urea hydrolysis and nitrification as bioprocesses in the MELiSSA nutrient loop, the nitrifying compartment of MELiSSA needs to be supplemented with appropriate nonpathogenic ureolytic bacteria, establishing a urea hydrolytic and nitrifying community (Hendrickx and Mergeay, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, growth rates were dependent on growth media, motility, and the bacterial species and strain, with a recent report suggesting that the motility of the bacteria is the primary cause of this discrepancy (Benoit and Klaus, 2007). While a synthetic community of N. europaea, N. winogradskyi, and Cupriavidus pinatubonensis and the respective pure cultures have recently been shown to withstand storage on an unmanned spaceflight in low Earth orbit for 44 days (Lindeboom et al, 2018), the effect on active cultures is unmapped. In this study, reduced gravity was simulated through clinorotation, with hardware typically utilized for in-flight experiments with active cultures.…”
Section: Introductionmentioning
confidence: 99%